Real-life study of the accuracy of tools for assessing fitness to drive after non-progressive acquired brain injury: a multi-centric study protocol (PREVAC study) - Rosier, Clothilde; Colliot, Pascale; Gabaude, Catherine (Frontiers in Human Neuroscience, 2025)
Non-progressive acquired brain injury can cause cognitive and behavioral damage. These disorders may hinder the driving abilities of affected individuals, increasing crash risk. Consequently, driving license regulations have required people who suffer from brain injury to be examined by an approved doctor for their driving license to remain valid. The decree of March 28, 2022 requires that approved doctors consider elements of patients’ multiprofessional evaluation, but mentions neither the on-road driving assessment nor the neuropsychological assessment. However, these assessments are an integral part of the good practice recommendations certified by the French National Authority for Health. Practitioners in rehabilitation centers are used to applying the main recommendations despite the lack of consensus about the methods and tools used. Given these new regulations and the wide variety of real-life practices, this multicenter study aims to investigate the accuracy of tools for driving skill evaluation to guide professional practices. The cross-sectional study will investigate the sensitivity and specificity of both neuropsychological tests and an on-road assessment grid (Test Ride for Investigating Practical fitness to drive), through concordance analysis between the opinions expressed by professionals and between tools. Then, a cohort study will propose longitudinal follow-up of the drivers at 6 and 12 months in order to determine the predictive performance of the various assessments in terms of road risk, and to explore the relevance of educational support on driving habits and behavior. In this context, the quality of the decision-making process for maintaining a driving license is a major issue in limiting the road risk. As part of the measures issued by the Interministerial Road Safety Committee in 2023 aimed at “better detecting, assessing and monitoring unfitness to drive”, this study presents a challenge in terms of supporting public policies. It aims to harmonize the multiprofessional evaluation recently made mandatory, in order to better inform the approved doctor’s opinion.